Recombinant Osteopontin Stabilizes Smooth Muscle Cell Phenotype via Integrin Receptor/Integrin-Linked Kinase/Rac-1 Pathway After Subarachnoid Hemorrhage in Rats. Issue 5 (May 2016) - Wu, Jiang; Zhang, Yang; Yang, Peng; Enkhjargal, Budbazar; Manaenko, Anatol; Tang, Jiping; Pearce, William J.; Hartman, Richard; Obenaus, Andre; Chen, Gang; Zhang, John H.
Abstract : Background and Purpose—: Recombinant osteopontin (rOPN) has been reported to be neuroprotective in stroke animal models. The purpose of this study is to investigate a potential role and mechanism of nasal administration of rOPN on preserving the vascular smooth muscle phenotype in early brain injury after subarachnoid hemorrhage (SAH). Methods—: One hundred and ninety-two male adult Sprague-Dawley rats were used. The SAH model was induced by endovascular perforation. Integrin-linked kinase small interfering RNA was intracerebroventricularly injected 48 hours before SAH. The integrin receptor antagonist fibronectin-derived peptide Gly-Arg-Gly-Asp-Ser-Pro (GRGDSP), focal adhesion kinase inhibitor Fib-14, and Rac-1 inhibitor NSC23766 were administered 1 hour before SAH induction. rOPN was administered via the intracerebroventricular and nasal route after SAH. SAH grade, neurological scores, brain water content, brain swelling, hematoxylin and eosin staining, India ink angiography, Western blots, and immunofluorescence were used to study the mechanisms of rOPN on the vascular smooth muscle phenotypic transformation. Results—: The marker proteins of vascular smooth muscle phenotypic transformation α-smooth muscle actin decreased and embryonic smooth muscle myosin heavy chain (SMemb) increased significantly at 24 and 72 hours in the cerebral arteries after SAH. rOPN prevented the changes of α-smooth muscle actin and SMemb and significantly alleviated neurobehavioral dysfunction, increased the cross-sectional area and the lumen diameter of the cerebral arteries, reduced the brain water content and brain swelling, and improved the wall thickness of cerebral arteries. These effects of rOPN were abolished by GRGDSP, integrin-linked kinase small interfering RNA, and NSC23766. Intranasal application of rOPN at 3 hours after SAH also reduced neurological deficits. Conclusions—: rOPN prevented the vascular smooth muscle phenotypic transformation and improved the neurological outcome, which was possibly mediated by the integrin receptor/integrin-linked kinase/Rac-1 pathway. Abstract : Supplemental Digital Content is available in the text.